ANALISIS EFEKTIVITAS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI 14 PADANGSAMBIAN - Ida Bagus Gede Surya Abadi; Chindytia Chindytia; Ni Luh Ketut Ary Maharani; Komang Wida Yuniati; Ni Putu Indah Pramitha Dewi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the effectiveness of the implementation of School-Based Management (SBM) in improving the quality of education at SD Negeri 14 Padangsambian, viewed from the aspects of resource management, principal leadership, community participation, as well as curriculum and school program management. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, with the principal as the main informant, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data collection, data condensation, data display, and conclusion drawing. The results indicate that the implementation of SBM has been carried out in various aspects, such as learning processes, management of facilities and infrastructure, and collaboration with external parties, supported by participatory principal leadership and stakeholder involvement, which contribute to improving the quality of learning. However, its implementation has not been fully optimal due to several constraints, such as the suboptimal execution of programs and the limited adjustment of some teachers to established procedures. The novelty of this study lies in its contextual analysis of SBM implementation at the elementary school level, emphasizing the relationship between participatory leadership, community participation, and the effectiveness of school programs in sustainably improving the quality of education.